Exploring associations between adolescent sexual and reproductive health stigma and HIV testing awareness and uptake among urban refugee and displaced youth in Kampala, Uganda. Issue 3 (29th November 2019) - Logie, Carmen H.; Okumu, Moses; Mwima, Simon P.; Kyambadde, Peter; Hakiza, Robert; Kibathi, Irungu Peter; Kironde, Emmanuel; Musinguzi, Joshua; Kipenda, Claire Uwase
Abstract: Uganda, hosting over 1.3 million refugees, is a salient context for exploring HIV testing with urban refugee and displaced youth. We examined associations between stigma (HIV-related and adolescent sexual and reproductive health [SRH]-related) and HIV testing services awareness and HIV testing uptake among urban refugee and displaced youth in Kampala, Uganda. We implemented a cross-sectional survey with refugee and displaced adolescent girls and young women (AGYW) and adolescent boys and young men (ABYM) aged 16-24. We conducted exploratory and confirmatory factor analysis of an adolescent SRH stigma scale and identified a two-factor structure ("Sexual activity & pregnancy stigma", "Modern family planning & abortion stigma"). We conducted multivariable logistic regression analysis to determine the adjusted risk ratio for HIV testing services awareness and testing uptake. Among participants (n=445; mean age=19.59, SD=2.60; AGYW: n=333; 74.7%), two-thirds were aware of HIV testing services in their community and over half (56.0%) had received a lifetime HIV test. In adjusted multivariable regression analysis findings with AGYW: (a) higher sexual activity & pregnancy stigma and modern family planning & abortion stigma were associated with reduced odds of HIV testing services awareness, and (b) modern family planning & abortion stigma was associated with reduced lifetime HIV testing odds. Stigma was not associated with HIV testing awareness/uptake among ABYM. HIV testing services awareness among AGYW was lower than among ABYM, yet AGYW were more likely to have been tested and to experience adolescent SRH stigma as a testing barrier. Addressing adolescent SRH stigma may optimise AGYW's HIV testing.